2005
DOI: 10.1210/en.2005-0777
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and Serum Phosphorus Regulate Fibroblast Growth Factor 23 Expression and 1,25-Dihydroxyvitamin D Metabolism in Mice

Abstract: Fibroblast growth factor-23 (FGF-23) is a novel circulating peptide that regulates phosphorus (Pi) and vitamin D metabolism, but the mechanisms by which circulating FGF-23 itself is regulated are unknown. To determine whether the serum FGF-23 concentration is regulated by dietary intake of Pi, we fed wild-type (WT), Npt2a gene-ablated (Npt2a(-/-)), and Hyp mice diets containing varying Pi contents (0.02-1.65%). In WT mice, increases in dietary Pi intake from 0.02-1.65% induced a 7-fold increase in serum FGF-23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
254
2
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 387 publications
(276 citation statements)
references
References 39 publications
15
254
2
5
Order By: Relevance
“…Because inorganic phosphate has been shown to induce Fgf23 expression in osteocyte-like IDG-SW3 cells (40), it is possible that the influx of phosphate from the diet may regulate circadian Fgf23 expression; however, previous in vivo studies failed to demonstrate an acute effect of dietary phosphate on FGF23 induction (41,42), making this concept unlikely to be operative. Despite the lack of an increase in FGF23 levels in response to an acute phosphate load, it has been well established that a chronic phosphate load causes elevations in FGF23 levels (43). Consistent with previous reports, we detected a significant increase in skeletal Fgf23 expression in mice fed a high phosphate diet, but this increase was not associated with sympathetic activation because the concomitant administration of PRO did not affect Fgf23 expression.…”
Section: Discussionsupporting
confidence: 90%
“…Because inorganic phosphate has been shown to induce Fgf23 expression in osteocyte-like IDG-SW3 cells (40), it is possible that the influx of phosphate from the diet may regulate circadian Fgf23 expression; however, previous in vivo studies failed to demonstrate an acute effect of dietary phosphate on FGF23 induction (41,42), making this concept unlikely to be operative. Despite the lack of an increase in FGF23 levels in response to an acute phosphate load, it has been well established that a chronic phosphate load causes elevations in FGF23 levels (43). Consistent with previous reports, we detected a significant increase in skeletal Fgf23 expression in mice fed a high phosphate diet, but this increase was not associated with sympathetic activation because the concomitant administration of PRO did not affect Fgf23 expression.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, dietary consumption of phosphate was shown to increase serum FGF23 level in both uremic rats and non-uremic mice (10)(11)(12). In healthy individuals, increased dietary phosphate load has been reported to increase the serum level of FGF23 (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Nutritional studies have revealed that the dietary restriction of phosphate intake results in decreased plasma levels of PTH by direct or indirect effect of plasma PO 4 3-levels [2] and that there occurs a delayed or improved secondary hyper-parathyroidism independent of plasma levels of Ca 2? or calcitriol.…”
Section: Basic Conceptsmentioning
confidence: 99%